PENGUATAN MANAJEMEN DAN PRODUKSI BATIK JEMBATAN AKAR DI PESISIR SELATAN - Adila Adisti; Chairunnisya Chairunnisya; Imam Gracia Marshall (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
The development of the creative batik industry in Pesisir Selatan Regency faces challenges regarding production and marketing, particularly within the Jembatan Akar Batik Artisan Group. This community service program aimed to enhance the partners' self-reliance and competitiveness in navigating business competition. Implementation methods included Focus Group Discussions (FGD) for problem mapping, training on motif design and batik coloring techniques, digital marketing mentoring, and the provision of production equipment. The results demonstrated an improvement in the partners' ability to create new batik motif compositions based on local wisdom. The partners were successfully able to rebrand their products and actively manage marketing through Instagram, resulting in expanded market reach and an increased volume of orders from new customers. This community service program proved effective in strengthening the production capacity and marketing strategies of the Jembatan Akar Batik Artisan Group.Keywords: Jembatan Akar Batik, FGD, Product Innovation, Digital Marketing, Community Empowerment.